Internet and Politics: Evidence from U.K. Local Elections and Local Government Policies - Alessandro Gavazza; Mattia Nardotto; Tommaso M. Valletti (Center for Economic Studies and ifo Institute (CESifo), 2017)
We empirically study the effects of broadband internet diffusion on local election outcomes and on local government policies using rich data from the U.K. Our analysis suggests that the internet has displaced other media with greater news content (i.e., radio and newspapers), thereby decreasing voter turnout, most notably among less-educated and younger individuals. In turn, we find suggestive evidence that local government expenditures and taxes are lower in areas with greater broadband diffusion, particularly expenditures targeted at less-educated voters. Our findings are consistent with the idea that voters' information plays a key role in determining electoral participation, government policies and government size.
Keywords: D72; 330